Formación en valores mediante el proceso educativo en los niños de la Escuela de Educación Básica Dr. Humberto Alvarado Prado - Rojas Parraga, Vanessa Darine (2020)
The objective of this work was to determine the nature of the training in values through the educational process in children of the Dr. Humberto Alvarado Prado School of Basic Education, its importance, theoretical concepts and routes that favor its execution, so To carry out this objective, a bibliographic review was developed in which works prepared by different authors were analyzed, among them, undergraduate work, doctorate and articles published in scientific journals of recognized influence. The values are linked to morality, referred to as a technique of norms, principles, ideals and ways, which also state the interests and motives of the subjects in society, so that educational institutions occupy the primary part within the set of influences educational programs involved in the training of children, because the educational process takes place in the classroom and in the other environments where students participate. Therefore, the commitment of the family is of the utmost importance, since it directs the first steps of the infant, who establishes his personality with the relations that he constitutes with his surroundings and members of the community, which will allow him to be able to live in community reaching his integral development.